Integration of coplanar (Ba,Sr)TiO3 microwave phase shifters onto Si wafers using TiO2 buffer layers - Kim, KB; Yun, TS; Lee, JC; Kim, HS; Kim, HG; Kim, ID (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
In this paper, a Ba0.6Sr0.4TiO3 (BST) tunable phase shifter with TiO2 films as microwave buffer layer between BST and silicon (Si) substrates is presented. The TiO2 buffer layer is grown by atomic layer deposition (ALD) onto Si substrate followed by pulsed laser deposition (PLD) of BST thin films onto the TiO2 buffer layer. The phase shifter fabricated on BST films grown on TiO2/Si substrate shows a good figure of merit (FOM) of 75.4 degrees/dB by exhibiting improved tunablity while retaining an appropriate dielectric Q as compared to 55.1 degrees/dB of BST/MgO structure. The TiO2 buffer layer grown by ALD enables successful integration of BST-based microwave tunable devices with high resistive Si wafer.
Keywords: THIN-FILMS; TA2O5